Paradoks Demokratisasi dan Liberalisasi Pasar terhadap Gerakan Anti-Korupsi di Negara Berkembang - Ahmad Khoirul Umam (Global South Review, 2014)
The package of neoliberal reforms involving three main components namely democratization, market liberalization, and the creation of good governance, has often adopted by a number of developing countries in order to overcome their prolonged political and economic crises. The policies which are often promoted by international donor agencies have been expected to streamline the transformation processes in the developing countries to establish a more powerful, well established and stable countries in economics and politics. However, experiences in developing countries actually showed the opposite trends, where the concept of market structure strengthening and the reduction of state authority in the public sector have often resulted in the widening loopholes and opportunities for more systematic and structured corruption practices.In addition, the democratization agenda has also often facilitated the old groups of interests to get back to control of the reformed political system leading to the symptoms of neo-patrimonialism in the process of democratic transition. The impact of these symptoms is the anti-corruption agenda inclines to become more vulnerable to manipulation, intervention, and political pressures. To eliminate such trends, it needs the presence of strong leadership factor backed up by an established surveillance system in order to encourage the 'rule of law' as the supreme commander in the transformation and democratic transitional processes which are usually haunted by various turbulences. This article completely uses a literature approach by analysing secondary data from books and journals in order to look at the dynamics and theoretical debates on pros and cons of the implementation of neo-liberal policies for developing countries’ anti-corruption agenda.